2006
DOI: 10.1002/ejoc.200600541
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Range Effects in the Metalation/Boronation of Functionalized 1,4‐Dihalobenzenes

Abstract: Keywords: Metalation / Long-range inductive effects / Substituent effects / Buttressing effects / Aryl halides / Aryl boronic acidsThe lithiation/boronation of 1,4-dihalobenzenes (Hal = F, Cl, Br) bearing various functional groups in the 2-position was investigated using lithium diisopropylamide (LDA) as the metalating agent and trialkyl borate B(OR) 3 (R = Et, iPr) as the electrophile. It was demonstrated that sufficient steric hindrance precludes effective ortho-lithiation at the 3-position. In such cases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Clearly, the lithiation of the (3‐Br‐5‐OMeC 6 H 3 )B(OR) 3 Li complex is not effective even at higher temperatures (ca. –15 °C), which confirms the reputation of the methoxy group being only weakly activating and/or anion stabilizing when located at a remote meta position,27,28 especially in comparison with fluorine 29,30…”
Section: Resultssupporting
confidence: 65%
“…Clearly, the lithiation of the (3‐Br‐5‐OMeC 6 H 3 )B(OR) 3 Li complex is not effective even at higher temperatures (ca. –15 °C), which confirms the reputation of the methoxy group being only weakly activating and/or anion stabilizing when located at a remote meta position,27,28 especially in comparison with fluorine 29,30…”
Section: Resultssupporting
confidence: 65%
“…It can be prepared readily from 1,2,4-tribromobenzene by using Br-Li exchange in THF at -105°C, but the reaction suffers from poor selectivity and possible side reactions, which reduce the yields of the desired 2,5-dibromo-substituted benzenes to ca 50 %. [12] The attempted deprotonation of 1 with the use of LTMP activated with PMDTA in THF at ca -100°C failed, but the reaction proceeds effectively over a few minutes at -80°C. Under these conditions, 1-Li is stable for at least 1 to 2 h. Typically, slow decomposition manifested by gradual darkening of the reaction mixture starts above -70°C, and the rapid degradation accompanied with a substantial temperature jump is observed at ca -60°C.…”
Section: Resultsmentioning
confidence: 98%
“…56 It has been demonstrated that sufficient steric hindrance precludes effective ortho-lithiation at the 3-position. In such cases, a strong meta-directing effect of an oxygen-or sulfur-based substituent (OMe, OSiMe 3 , SMe), resulting in the preferred formation of 2,6-disubstituted 1,4-dihalobenzenes has been observed.…”
Section: Organometallic Speciesmentioning
confidence: 99%